Startups’ Discursive and Communication Strategies on Social Media - Fernández Torres, María Jesús; Rando Cueto, Dolores; del Pino Rodríguez-Vera, Ainhoa (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Social networks have emerged as essential tools for start-ups seeking to differentiate in competitive markets. This research analyses digital communication strategies adopted by 181 Andalusian start-ups to identify patterns of success and areas of improvement in their social media management. Using Fanpage Karma analysis tool, data was gathered during six months in 2024. Indicators such as engagement, post frequency, audience interaction and effectiveness of content formats were evaluated.This study reveals trends in visual and textual content, posting consistency and audience engagement strategies and offers useful insights for researchers and entrepreneurs interested in boosting their impact on social networks.